LITERATURE REVIEW: THE EFFECT OF PROJECT-BASED LEARNING ON STUDENT MOTIVATION AND ACHIEVEMENT IN SCIENCE - Firdausih Firdausih; Aslan Aslan (Indonesian Journal of Education (INJOE), 2025)
Project Based Learning (PBL) is a student-centred educational approach where learners acquire knowledge and skills through in-depth investigation of complex and authentic problems or challenges. In PBL, students are actively engaged in a long-term learning process, working collaboratively to design, develop and produce real products or solutions, while integrating multiple disciplines and developing 21st century skills. The research method in this study is literature. The results showed that PBL was consistently positively correlated with increased student intrinsic motivation and academic achievement in science. However, the review also identified challenges in implementing PBL, including the need for careful planning and adequate support. Thus, PBL offers a promising approach to improving the quality of science education, with significant potential to prepare students for the real-world demands of the modern era.